POTENTIAL BENEFITS OF WEB-BASED IDEA MANAGEMENT SYSTEM BASED ON PRACTICAL EVIDENCE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
During the last decade software developers have put increasing focus on developing information systems supporting decision making, collaboration, knowledge and idea management. Idea management systems (IMS) - manageable systematic tools to generate and evaluate ideas - are an important element within this trend.   Web-based IMS are used by many well-known organizations, e.g. Volkswagen, Cisco, Microsoft, Lidl, GE Healthcare, Nestle, Procter and Gamble, Tchibo, Henkel, Roche, Fujitsu, Boeing, Goodyear, Xerox, Panasonic, Pentax, Siemens, Virgin trains etc. Although the research on web-based IMS and how these systems are applied practically is very limited. Therefore, the authors of this research aim to explore practical web-based IMS application and potential benefits. Research aim is based on theoretical and empirical approaches to deliver understanding on how web- based IMS materializes and what are potential benefits from its application to increase organizational effectiveness. Web-based IMS application will be researched by analysing separate use-cases and reprocessing the results using content analysis. 1st step – analysis of 100 users cases based on available information about application cases from homepages of web-based IMS developers. 2nd step –analysis of the results from 1st step. The analysis will be conducted by analysing information from protocols of use-cases. Protocols will be organized as category maps. Category maps are based on literature studies (finding deductive elements with available data), on data (inductive elements) and organized around Adaptive Structuration Theory elements. As the 3rd step use case descriptions and comparison will be applied. The results show that the web-based IMS are universally applicable in different organisation for fulfilling the various tasks. Benefits of web-based IMS application could be divided into 4 main groups towards benefits of- the idea management, innovation management, cooperation, and overall effectiveness of organization. Academic contribution: (1) most extensive research of web-based IMS based on 100 use cases; (2) empirical overview of potential benefits of web-based IMS application; (3) Development of IMS use case analysis protocol applicable in further researches. Practical contribution: (1) Empirical overview of web-based IMS application experience in various organizations that can stimulate the application of web-based IMS in other organizations and to deliver benefits to organization; (2) The benefits are summarized and can help in decision making whether to apply and implement a web- based IMS in and an organization.